The performance of corporate alliances: Evidence from oil and gas drilling in the Gulf of Mexico - Beshears, John (Journal of Financial Economics, 2013)
I use data on oil and gas drilling in the Gulf of Mexico to measure how a corporate alliance—a group of firms that jointly develops an offshore tract—performs relative to a solo firm. I employ a regression discontinuity strategy based on bids in first-price sealed-bid auctions for the rights to develop leases. By focusing on leases where one organizational form narrowly outbids the other, I measure drilling outcomes while controlling for the endogenous matching of projects and organizational forms. Solo firm leases are less profitable than alliance leases because alliance members combine their information and expertise.